The line-of-balance programme on repetitive works: case study / Shaharuddin Abdul Samad - Abdul Samad, Shaharuddin (1996)
As if repetitive works might be construction of a housing project in manufacturing of computer components' products and such that has identical unit, one powerful technique had being developed. This technique is known as line-of-balance method and can applied in various fields with repetitive works such been mentioned above. To fulfil the requirement for the degree of Bachelor in Engineering with Hons (Civil), thus the author will only emphasise on the construction industries. Undoubted, in construction industries , there are many repetitive works involve such as residential housing project construction of prestressed beam, delivery of materials from plant to the site, construction of high rise building et cetera. Living in technology of information era now, everything is just on our fingers' tip, thanks to the computer and its software that available anywhere. In making the repetitive works done with more efficiently, effectively and reduce time cost, a computer programme has been developed based on the Line-of-Balance Method. The programme is developed interactively, as the user will feel conveniently to use it The user is then being asked to open two files to restore all the data. Eventually, the output will then can be used for analysing, controlling and lastly can make comparison between the developed programme and progress of the project on the site.